Contexto de trabalho e trabalho docente: investigação com professores de inglês de cursos particulares de Fortaleza/CE - Moura, Lucas Varella de (2014)
This work wishes to investigate the work context of English teachers from private courses in Fortaleza/CE from their own perceptions. The interest for this research came from the author’s previous experience as both English teacher and work psychologist, in one of those courses, observing the reality of these professionals and listening to their stories. Due to the lack of researches focused on this specific group, it was decided that this one would focus in defining the work context from the teachers’ perceptions, so that it could assist the process of future researches. Teaching work is an interactive process, teaching being understood as a particular kind of work on the human being, that is, an activity in which the workers dedicate themselves to the work’s “object”, which is another human being, in a fundamental way of human interaction. Work context is something that involves factors such as work environment, work relations, work process, work organization and workload. It expresses and synthesizes and objective part of the work world taking as its basis the interaction axis subject-activity-world. So, we consider “work condition or work context”, the group of variables that allow the characterization of quantitative dimensions of teaching as work time (daily, monthly, yearly), the number of mandatory hours in the classroom, number of students per class, teachers’ salary, etc. The data gathering was done through the use of an objective questionnaire called Work Context Evaluation Scale (WCES) which contemplates the following dimensions: Work Organization, Work Condition and Social-Political Relationships. The analysis was made according to the data obtained from the questionnaires and through the conversations occurred with the teachers, during the questionnaire application. According to the obtained results we can conclude the most of the teachers perceive as Good, their work context. The work organization was considered Regular. And, work condition and the social-professional relationships were both considered closer to Excellent.